Inflammatory Cells in Atypical Eruption of Lymphocyte Recovery Carry the Same Mutations as Neoplastic Myeloid Cells. (May 2020) - Prieto-Torres, Lucía; Chamizo, Cristina; Salgado, Rocio Nieves; Atance, Mireia; Soto, Carlos; Alonso Domínguez, Juan Manuel; Arquero, Teresa; Piris, Miguel Angel; Requena, Luis; Rodriguez-Pinilla, Socorro María
Abstract : Abstract: Cutaneous eruption of lymphocyte recovery (ELR) during bone marrow (BM) aplasia recovery after intensive chemotherapy has been reported in very few patients. The presence of skin rashes in patients with acute leukemia who are undergoing intensive chemotherapy and BM transplantation is a diagnostic challenge because of the clinical similarity between drug eruptions, infiltrates related to the relapse of the underlying disease, cutaneous graft-versus-host disease, and ELR. IDH1 mutations have been identified as a recurrent genetic anomaly in acute myeloid leukemia and myelodysplastic syndromes. However, until now, this IDH1 mutation has not been reported as being shared by myeloid cells and non-neoplastic inflammatory cells in this clinical setting. Here, we present the rare case of a woman diagnosed with myelodysplastic syndrome that evolved into an acute myelogenous leukemia with leukemic cutaneous infiltrate. The patient developed ELR after the intensive chemotherapy administered before BM transplantation. The IDH1 mutation was identified in BM cells and in myeloid and inflammatory cells in skin biopsies before allogeneic BM transplantation. We discuss the main aspects of the differential diagnosis of these cutaneous reactions in leukemic patients and the biological significance of the IDH1 mutation.